P.D.C.s.r.o. (1920-1955) - Petrová, Jarmila (Iluminace, 2012)
Information about the formation and activities of P.D.C.s.r.o. (Producers Distributing Corporation Ltd.) in 1920-1955. The company was involved in the rental of films.
Keywords: film distributors; film rental; archive funds